Kekerasan Verbal dalam cerpen Jagal karya Dorothea Rosa Herliany - Alexander Bala (Jurnal Lazuardi, 2021)
Verbal abuse has become a logical consequence of communication events in social interactions. This research examines verbal violence in the short story of Dorothea Rosa Herliany's Jagal. The research method used is the literature method with a qualitative descriptive approach. The theory used is the theory of verbal violence. The results of this study indicate that verbal violence in the short story Jagal by Dorothea Rosa Herliany occurs between the main character Karto and the local community in the form of phrases and sentences.